Toxicity of saponin isolated from Gymnema sylvestre R. Br. (Asclepiadaceae) against Culex tritaeniorhynchus Giles (Diptera: Culicidae) Japanese encephalitis vector mosquito in India - Elumalai, Kupppusamy; Dhanasekaran, Shanmugan; Krishnappa, Kaliamoorthy (Revista do Instituto de Medicina Tropical de São Paulo, 2012)
To determine the larvicidal activity of various extracts of Gymnema sylvestre against the Japanese Encephalitis vector, Culex tritaeniorynchus in Tamilnadu, India. To identify the active principle present in the promising fraction obtained in Chlorofom:Methanol extract of Fraction 2. The G. sylvestre leaf extracts were tested, employing WHO procedure against fourth instar larvae of C. tritaeniorhynchus and the larval mortalities were recorded at various concentrations (6.25, 12.5, 25.0, 50 and 100 µg/mL); the 24h LC50 values of the G. Sylvestre leaf extracts were determined following Probit analysis. It was noteworthy that treatment level 100 µg/mL exhibited highest mortality rates for the three different crude extracts and was significantly different from the mean mortalities recorded for the other concentrations. The LC50 values of 34.756 µg/mL (24.475-51.41), 31.351 µg/mL (20.634-47.043) and 28.577 µg/mL (25.159-32.308) were calculated for acetone, chloroform and methanol extract with the chi-square values of 10.301, 31.351 and 4.093 respectively. The present investigation proved that G. Sylvestre could be possibly utilized as an important component in the Vector Control Program.